Influence of traffic emissions on the composition of atmospheric particles of different sizes-Part 2: SEM-EDS characterization - K. Slezakova (2008)
In urban areas traffic is the major contributor to atmospheric particulate matter and exposure to these particles currently represents a serious risk to human health. The attention has been recently focused more on the particles of smaller sizes (PM(2.5)) which penetrate deeper in respiratory system causing severe health effects. Therefore, more information on PM(2.5) should be provided, namely concerning morphological and chemical characterization. Aiming further evaluation of the impact of traffic emissions on public health, this work evaluated the influence of traffic on the chemical and morphological characteristics of PM(10) and PM(2.5), collected at one site influenced by traffic emissions and at one reference site. Chemical and morphological characteristics of 1,000 individual particles were determined by scanning electron microscopy combined with energy dispersive spectrometer (SEM-EDS). Cluster analysis (CA) was used to identify different types of particles that occurred in PM, aiming the identification of the respective emission sources. Traffic PM(2.5) were dominated by particles composed of Fe oxides and alloys (67%) which were related to traffic emissions (this percentage was 3.7 times higher than at the background site); in PM(2.5-10) the abundance of Fe oxides and alloys were 20% and 0% for the traffic and background sites, respectively. Background PM(2.5) were mainly constituted by aluminum silicates (63%) related to natural sources (this percentage was 2.5 times higher than at the traffic site); the abundances of aluminum silicates in PM(2.5-10) were 74% and 73% for traffic and background sites, respectively. It was concluded that traffic emissions were mainly present in PM(2.5) (the percentage of particles associated to these emissions was 3.4 times higher than in PM(2.5-10)), while coarse particles were dominated by material of natural origin (the percentage of particles associated was 1.2 and 3.0 times higher than in PM(2.5) for traffic and background sites, respectively). Previous results obtained by proton induced X-ray emission (PIXE) were consistent with SEM-EDS analysis that showed to be very useful to complement elemental analysis of different PM(2.5) and PM(2.5-10).